SEKSUALITAS MANUSIA DAN MASALAH GENDER: DEKONSTRUKSI SOSIAL DAN REORIENTASI - Yulfita Raharjo (Populasi, 1997)
Up to now the residual product from the social construction of sexuality and gender is still considered as a reference by most of the society so that they put women in the subordinate position. In the sexuality sphere, the women's powerlessness is obviously seen as reflected in the constraint of sexual intercourse, violation, wives who take high risk of HIV/AIDS,and so on. Yulfita Raharjo reveals several sexuality lamenesses and gender problems. This writing,further, describes the solution of the problems through a deconstruction and reorientation in understanding the gender relationship, i.e. the partnership relation between men and women.